2008
DOI: 10.1071/ea05112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hormonal growth promotants on palatability and carcass traits of various muscles from steer and heifer carcasses from a Bos indicus - Bos taurus composite cross

Abstract: Abstract. The effect of several different hormonal growth promotant (HGP) implant strategies on the palatability and carcass traits of different muscles in beef carcasses was investigated using samples from heifer and steer carcasses from a Bos indicus composite breed. In experiment 1, there were seven different implant strategies evaluated in heifers that were given different combinations of up to three implants (implanted at weaning, during backgrounding and at feedlot entry). A total of 112 heifers were sla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…(4) The use of HGP results in a penalty of the order of three to six meat quality points on meat palatability, depending on the cut. Watson et al (2008c) reported that: (i) significant changes in carcass weight, skeletal maturity and marbling were associated with HGP use in both steers and heifers, with the effects being greater in steers; and (ii) in both heifers and steers, HGP use was associated with significant reductions in flavour, juiciness, tenderness and marbling. Thompson et al (2008bThompson et al ( , 2008c concluded that the effects of HGP use in reducing flavour, tenderness and overall palatability are much greater in beef from 100% B. indicus cattle than in beef from 50% B. indicus cattle, but that all implant strategies used caused a reduction in meat quality.…”
Section: Msa Grading Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) The use of HGP results in a penalty of the order of three to six meat quality points on meat palatability, depending on the cut. Watson et al (2008c) reported that: (i) significant changes in carcass weight, skeletal maturity and marbling were associated with HGP use in both steers and heifers, with the effects being greater in steers; and (ii) in both heifers and steers, HGP use was associated with significant reductions in flavour, juiciness, tenderness and marbling. Thompson et al (2008bThompson et al ( , 2008c concluded that the effects of HGP use in reducing flavour, tenderness and overall palatability are much greater in beef from 100% B. indicus cattle than in beef from 50% B. indicus cattle, but that all implant strategies used caused a reduction in meat quality.…”
Section: Msa Grading Systemsmentioning
confidence: 99%
“…highest to lowest, of five star (premium), four star (better than everyday), three star (good everyday) and no star (unsatisfactory). Watson et al (2008aWatson et al ( , 2008c reported that:…”
Section: Msa Grading Systemsmentioning
confidence: 99%
“…The use of HGPs has been studied extensively in the database (Thompson et al 2008a;Watson 2008;Watson et al 2008b), and in a range of associated experiments reported elsewhere. The result was an HGP penalty of the order of 3-6 MQ points on meat palatability, depending on the muscle which is further adjusted with aging.…”
Section: Hgp Implantsmentioning
confidence: 99%
“…psoas major, longisimuss dorsi thoraics and lumborum portions. Details of the procedure and the results can be found in Watson et al (2008b). In this trial, only the sensory (tenderness) scores were available.…”
Section: Q-2 Trial: Watson Et Al (2008b)mentioning
confidence: 99%
“…The studies considered in this meta-analysis are papers that have appeared in refereed journals for which estimates and standard errors are available, including the recent Australian studies (Hunter et al 2001;Thompson et al 2008aThompson et al , 2008bWatson et al 2008b;McIntyre et al unpubl. data) summarised in the Results section.…”
Section: Introductionmentioning
confidence: 99%